Factors Influencing The Transition Of Transaction Activities From Conventional To Financial Technology - Andri Ikhwana; Jeany Afreisca Safira (UNIVERSITAS PAKUAN, 2023)
Financial technology as a service innovation in the financial industry has become a means of transaction in the rapidly growing buying and selling transactions. Besides, it has become one of the alternative means of payment for consumers. This opportunity can be used as a business development opportunity for financial services for financial business providers. Changes in the transition from conventional payments to payments using financial technology services are influenced by various factors that support changes in transaction activities. This study aims to determine the factors influencing payment transaction activities, from conventional payments to payments using financial technology services. The research methodology involves various variables involved in it by using the factor analysis approach to determine factors that support the achievement of research objectives. It is supported by a sample of 100 respondents with various representative sample criteria to explain each factor involved in the research. The research results show that the transition of payment transaction activities from conventional methods to payment transactions with financial technology services is influenced by various variables. The variables included are information system flexibility, ideal, and value for use, ability, comfort, safety, interaction, activity, and length of transaction time.